NO2 functionalized coumarin derivatives suppress cancer progression and facilitate apoptotic cell death in KRAS mutant colon cancer. (25th August 2019) - Lin, Mei-Hsiang; Wang, Juo-Shan; Hsieh, Yi-Chen; Zheng, Jia-Huei; Cho, Er-Chieh
Abstract: Colon cancer is one of the most lethal cancers worldwide even with the significant progress made in screening techniques and therapeutic agents. Genetic mutations in tumors complicated the treatments, and the survival rate remains low for patients at late or metastatic stages. KRAS gene mutation which leads to failure of the EGFR targeted therapies stands for an example of the challenges in clinical sites. Therefore, development of novel agents for colon cancer treatment is in need. Natural and synthetic coumarin derivatives have been suggested with various biological activities with pharmacologic potential including anti-cancer capacity. Here in this study, five coumarin derivatives, include trifluoromethyl-, dimethoxy-, and/or nitro-substitutions at different positions, were synthesized. Their cancer inhibition potential was investigated in various cancer cell lines. Our data demonstrated that one nitro-coumarin derivate, 5, 7-Dimethoxy-4-methyl-6-nitro-chromen-2-one, exhibits cytotoxicity specifically towards colon cancer cells under competitive EC50 . Our results showed that this compound can effectively suppress colon cancer cells harboring either wild type or mutant KRAS genes, and that it could inhibit short-term proliferation, long term proliferation, and migration capacities of cancer cells. Finally, we demonstrated that this coumarin derivate facilitates cancer cell death through activation of apoptosis pathway. Our results suggest that this coumarin derivate is a promising lead drug worth further investigation and development for future cancer treatment. Highlights: Coumarin derivatives were synthesized and examined in different human cancer cells. A novel compound exhibited cytotoxicity specifically towards colon cancer cells. It can inhibit short-term and long-term cancer cell proliferation. It can suppress migration capacity of colon cancer cells. It can facilitate cancer cell death through activation of apoptosis pathway.